Comparison of perioperative outcomes in frail patients following multilevel lumbar fusion surgery with and without the implementation of the enhanced recovery after surgery protocol - Cui, Peng; Wang, Shuaikang; Wang, Peng; Yang, Lijuan; Kong, Chao; Lu, Shibao (Frontiers in Surgery, 2022)
Background: The enhanced recovery after surgery (ERAS) is an evidence-based multimodal perioperative management designed to reduce length of stay (LOS) and complications. The purpose of present study are to evaluate the return of physiological function, length of stay, complications, pain score and clinical efficacy in frail elderly patients undergoing multi-segment fusion surgery after the implementation of ERAS protocol. Methods: Frail Patients older than 75 years undergoing multi-level lumbar fusion surgery from January 2017 to December 2018 (non-ERAS frail group) and from January 2020 to December 2021 (ERAS frail group) were enrolled . Propensity score matching for age, sex, body mass index and smoking status was performed to keep comparable characteristics . Further recovery of physiological function, LOS, complications, pain score and clinical efficacy were compared. Results: There were 64 pairs well-balanced patients and the baseline data were comparable between two groups. There was significant improvement in recovery of physiological function (10.65 ± 3.51 days versus 8.31 ± 3.98 days, p = 0.011) and LOS (12.18 ± 4.69 days versus 10.44 ± 4.60 days, p = 0.035), while no statistical discrepancy was observed in complications among groups, which indicating the favorable outcomes after the implementation of ERAS. Further analysis indicated that more patients meeting a minimally clinical important difference (MCID) for visual analogue score (VAS) for leg and Oswestry Disability Index (ODI) in ERAS frail group. With regard to postoperative pain, the pain score was higher in ERAS frail on POD 1 (4.88 ± 1.90 in ERAS frail group versus 4.27 ± 1.42 in non-ERAS frail group, p = 0.042), while there were no significant discrepancy on POD 2 (3.77 ± 0.88 in ERAS frail group versus 3.64 ± 1.07 in non-ERAS frail group, p = 0.470) and POD 3 (3.83 ± 1.89 in ERAS frail group versus 3.47 ± 1.75 in non-ERAS frail group, p = 0.266). Conclusions: We found a significant improvement in LOS, recovery of physiological function and clinical efficacy after the implementation of ERAS in elderly and frail patients undergoing multi-level lumbar fusion surgery, while there was no statistical discrepancy in complications, 90-day readmission and postoperative pain.